Adsorptive Removal of Crystal Violet Dye from Aqueous Solution Using a Vermiculite-Based Geopolymer - Ampfarisaho Marubini; Rirhandzu Mhlarhi; Joshua Nosa Edokpayi (Scientific African)
The removal of hazardous dyes from industrial wastewater is crucial for environmental protection and public health. In this study vermiculite based geopolymer, herein termed VBG, was used as effective adsorbent to remove crystal violet (CV) dye from aqueous solution. VBG was characterized using a Fourier transform infrared (FT-IR) spectrometer, scanning electron microscope (SEM), with energy dispersive X-ray spectroscopy (EDX) and Brunauer Emmett, Teller (BET). Various experimental factors, including contact time, adsorbent dosage, initial dye concentration, adsorbate pH, temperature, and change in water chemistry were examined on the efficiency of CV removal. The point of zero charge was also evaluated. Optimum CV removal conditions were attained at 15 min. The pseudo-second order and Temkin models provided the best description of the data from the kinetic and isotherm models respectively. The thermodynamic parameters, ΔH and ΔS indicate that the adsorption process was endothermic and spontaneous. The sorbent was desorbed using 0.1 M NaOH solution and after 5 regeneration cycles, it was still able to remove above 71 % of the CV dye. Based on the data obtained, VBG may be explored as an affordable adsorbent for CV dye sequestration.